A minimum price per unit of alcohol: A focus group study to investigate public opinion concerning UK government proposals to introduce of new price controls to curb alcohol consumption. - Hagger, Martin; Lonsdale, A.; Hardcastle, S. (BioMed Central Ltd, 2012)
UK drinkers regularly consume alcohol in excess of guideline limits. One reason for this may be the high availability of low-cost alcoholic beverages. The introduction of a minimum price per unit of alcohol policy has been proposed as a means to reduce UK alcohol consumption. However, there is little in-depth research investigating public attitudes and beliefs regarding a minimum pricing policy. The aim of the present research was to investigate people's attitudes and beliefs toward the introduction of a minimum price per unit of alcohol policy and their views on how the policy could be made acceptable to the general public.